2020
DOI: 10.3389/fimmu.2020.607211
|View full text |Cite
|
Sign up to set email alerts
|

Factor H Autoantibodies and Complement-Mediated Diseases

Abstract: Factor H (FH), a member of the regulators-of-complement-activation (RCA) family of proteins, circulates in human plasma at concentrations of 180–420 mg/L where it controls the alternative pathway (AP) of complement in the fluid phase and on cell surfaces. When the regulatory function of FH is impaired, complement-mediated tissue injury and inflammation occur, leading to diseases such as atypical hemolytic uremic syndrome (a thrombotic microangiopathy or TMA), C3 glomerulopathy (C3G) and monoclonal gammopathy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…At variance with aHUS patients, we did not observe a correlation between the presence of FHAAs and homozygosity for CFHR1 del in C3G/IC-MPGN patients, consistent with previous data ( Blanc et al, 2015 ; Valoti et al, 2019 ; Zhang et al, 2020 ). In addition, the prevalence of the common SVs ( CFHR3-CFHR1 del or CFHR1-CFHR4 del) did not differ between patients and healthy controls, indicating that common SVs are not risk factors for C3G/IC-MPGN.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At variance with aHUS patients, we did not observe a correlation between the presence of FHAAs and homozygosity for CFHR1 del in C3G/IC-MPGN patients, consistent with previous data ( Blanc et al, 2015 ; Valoti et al, 2019 ; Zhang et al, 2020 ). In addition, the prevalence of the common SVs ( CFHR3-CFHR1 del or CFHR1-CFHR4 del) did not differ between patients and healthy controls, indicating that common SVs are not risk factors for C3G/IC-MPGN.…”
Section: Discussionsupporting
confidence: 92%
“…IC-MPGN has typically been linked to the activation of the complement CP following infections, autoimmune diseases or malignancies, while C3G has primarily been linked to activation of the complement AP ( Sethi and Fervenza, 2011 ). In both C3G and IC-MPGN, genetic defects in complement AP genes like CFH , C3 , CFI , and CFB ( Servais et al, 2012 ; Iatropoulos et al, 2016 , 2018 ), and acquired factors, such autoantibodies that stabilize the C3 convertase complex C3bBb (called C3-nephritic factors, C3NeFs) or against FH, FB and C3b have been identified ( Zhang et al, 2012 , 2020 ; Blanc et al, 2015 ; Marinozzi et al, 2017 ; Donadelli et al, 2018 ). These findings indicate that the dysregulation of the complement AP may underlie the pathogenesis of both diseases ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, it was first reported that anti-complement factor H autoantibodies (FH autoAb) can cause complement system dysregulation leading to aHUS through neutralization of the complement factor H regulatory protein [ 3 ]. FH autoAbs have since been found in 10.9% of aHUS patient cohorts in North America, consistent with reports from Europe, and in 55.8% of the patients in the aHUS database in India, with children aged four to seven most affected [ 4 - 5 ].…”
Section: Introductionsupporting
confidence: 82%
“…FH is the main inhibitor of the alternative pathway, which is continuously activated in plasma but also in an amplification loop of the classical and lectin pathways. Genetic variants as well as autoantibodies affecting the C-terminal domains of FH impair the simultaneous binding of FH to sialic acid and C3b and are associated with complement-related diseases such as atypical hemolytic uremic syndrome, age-related macular degeneration and C3 glomerulopathy ( 12 , 13 ). Decreased levels of the FH ligand sialic acid might result in the same outcome.…”
Section: Introductionmentioning
confidence: 99%